Edward Augustus Inglefield (1820-1894) - Stone, Ian R. (ARCTIC, 1987)
Inglefield was one of the large number of Royal Naval officers whose careers were advanced by participation in the Franklin search. This was a highly satisfactory time for such men as it provided ample opportunity for employment in a rigorous environment and in a cause in which there was a gratifyingly high level of public interest. The North was certainly much healthier than the other contemporary area in which naval initiative could be displayed - off the African coast in the suppression of the slave trade. In the Franklin search Inglefield did not, however, achieve the highest distinction. He visited the Arctic three times, but his second and third voyages were simply means of communications with Sir Edward Belcher's 1852-1854 expedition. His first voyage, on the other hand, did have one solid achievement that greatly redounded to Inglefield's credit, and this is sufficient reason for devoting attention to him. . Inglefield was one of Lady Franklin's happier appointments. The expedition differed from the other expeditions in which she was active in that Inglefield was, himself, to "provide a crew, and what other fitments the vessel needed" for the voyage, on return from which the ship was to become his own property. . The plan was to search Jones Sound and the west coast of Baffin Bay for traces of Franklin. The west coast of Greenland was examined on the outward voyage, and new discoveries of geographical features were made. Smith Sound was penetrated to a latitude of 78 28 21 N, "therefore placing the Isabel about 140 miles further than had been reached by any previous navigator, of whom we have any records." . Jones Sound was investigated as far as 84 10 W, and then a visit was made to Beechey Island in Lancaster Sound, where communication was established with H.M.S. North Star, the depot ship of Belcher's expedition. Inglefield "pressed upon Captain Pullen the acceptance of all my surplus stores and provisions," but this offer was declined as Pullen was "prohibited by his commanding officer from in any ...